Predicting implementation of the PAX Good Behavior Game + MyTeachingPartner interventions - Braun, Summer S.; Bradshaw, Catherine P.; Beahm, Lydia A.; Budavari, Alexa C.; Downer, Jason; Ialongo, Nicholas S.; Tolan, Patrick H. (Frontiers in Psychology, 2023)
Effective classroom management is critical to creating a classroom environment in which social, emotional, and academic learning can take place (Evertson & Weinstein, 2011). Yet, many teachers receive insufficient pre-service training in classroom management practices, making this a prime area for professional development upon entry into the classroom. It is also well-known that teachers’ implementation of evidence-based programs in schools is notably low and may be impacted by a variety of characteristics (Domitrovich et al., 2008), but less is known about whether there are unique factors predicting early career teachers’ implementation of evidence-based programs. The present study investigated the association between early career, early elementary teachers’ occupational health (job stress, burnout, and perceived teaching ability) and perceptions of program feasibility in relation to their implementation dosage and quality in the combined PAX Good Behavior Game (GBG) and MyTeachingPartner (MTP) intervention. Results from ninety-four intervention teachers from a randomized controlled trial indicated that teachers participated in more MTP coaching cycles when they reported that the combined PAX GBG + MPT program was feasible. Although there were no main effects of occupational health on implementation, the associations between job stress and implementation quality were moderated by perceptions of feasibility, highlighting the complexity of factors impacting the implementation of evidence-based programs at school.